Interview with Mary Nash - Blasco, Inmaculada (Filanderas, 2019)
Mary Nash was one of the first historians who, in a context certainly adverse, affirmed and showed that women had also been protagonists of the past. In addition to promoting the process of academic institutionalization of this field of historical research, he approached feminist historiographical debates to Spanish historians and opened central lines of research in the history of women and gender for contemporary Spain: women and anarchism, women and movement worker, historical feminism, women in the Civil War, women, colonialism and postcoloniality, women, gender and Transition to democracy.
Keywords: Mary Nash; Feminism; Women history; Gender; University